Islam Dan Diskriminasi Lgbt Dampaknya Pada Penurunan Ekonomi - Yusnani; Haslina, Welsi; Magfirah (Akuntansi dan Manajemen, 2020)
Sexual relations between members of the same sex article 292 of the Indonesian Criminal Code (KUHP) regulates that adults who commit immoral acts of same-sex homosexuals who are not yet adults are threatened with imprisonment for a maximum of five years. Islam regulates both the Qur'an and Al-Hadith in qath'i (firm) and muhkamat (clearly legal provisions) strongly opposed this behavior. Allah calls homosexual acts fashyyah (vicious bandages) accursed. This study applied the concept of the role of the clerics of the Health Service Coordinating Board in the prevention of homosexual HIV / AIDS in the city of Padang, a method for overcoming a combination of qualitative and quantitative approaches resulting in policy recommendations. To describe the analysis of this research used descriptive method of prescriptive synthesis analysis. The government has not yet implemented the Draft Law article 292 The proposal applies a criminal law of five or a maximum of ten years, both adults and children or is punished equally with adultery both whipping law for single whips for married people. The regional economy will rise if the Islamic economy is upheld, investors can advance if they intend to improve the welfare of living together.